Efforts of the Educational Unit through the Police Go to School Program in the Legal Jurisdiction of Cimahi Police - Noviansyah, Muhammad Mahdi Heavany (Advances in Police Science Research Journal, 2024)
The problem of traffic attitudes is already a phenomenon that is common in big cities in developing countries. An increase in the number of vehicles that is faster than the increase in road infrastructure results in various traffic problems, for example traffic violations that lead to accidents. The cause of the accident in the Cimahi Regional Police Jurisdiction is due to the lack of discipline of the community in implementing and obeying traffic rules. This study aims to analyze and describe the efforts and factors that influence the implementation of the Police Go to School program by the Dikyasa Unit. The location of the research was at the Cimahi Police Station with a focus on community unit education in the area. This study uses qualitative methods with descriptive analysis techniques. Using triangulation of data 4 (four) kinds of techniques, namely sources, theories and techniques as well as primary, secondary and tertiary data sources. Data validity is data reduction, data display, conclusion drawing and verification. This research is based on communication theory, 6M management theory, socialization theory, and management planning theory. The approach used in this study is a qualitative approach and field research methods. Data collection techniques used in the study were interviews, observation and document review. The results of the study indicate that the Police Go to School activities have been carried out according to procedures and planning. The Police Go to School program as a precaution against traffic violations is carried out by Kanit Dikyasa through various approaches so that the Police Go to School program can be well received by high school students. So that approaches outside the Police Go to School program can work towards establishing connections between the police and high schools in the Cimahi Regional Police Legal Area. To optimize the Police Go to School activities, it is necessary to increase the number of personnel for the Dikyasa Unit by making mutations in functions, sending personnel to attend vocational education, the material submitted must detail the factual problems faced by the community, the media used are adjusted to the communicant and use information technology that is more modern so that it can be accepted by millennials in the Police Go to School program as a preventive effort against traffic violations committed by high school students.